Karakteristik Enkapsulat Ekstrak Etanol Kulit Kopi Robusta (Coffea canephora) dengan Perbandingan Maltodekstrin dan Gum Arab - Rahayu, Desak Made Ayu Gayatri; Yusasrini, Ni Luh Ari; Puspawati, Gusti Ayu Kadek Diah (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 3 (2024): Jurnal ITEPADO - 10.24843/itepa.2024.v13.i03.p08, 2024)
Extracts from robusta coffee skin (Coffea canephora) contain antioxidant compounds such as phenols, flavonoids, beta-carotene, anthocyanins, and vitamin C. Because viscous extracts have limitations in application, further processing is required to convert them into powder using encapsulation technology. Maltodextrin is often used as a coating agent in encapsulation, but due to its low emulsifying properties, its combination with gum arabic is used to create a stable emulsion. The aim of this research is to determine how variations in the ratio between maltodextrin and gum arabic affect the encapsulation characteristics of Robusta coffee husk ethanol extract, as well as to determine the appropriate ratio to produce encapsulation with the best characteristics. This research used a Completely Randomized Design (CRD) with one factor, namely variations in the ratio of maltodextrin (M) and gum arabic (G), with a ratio of (10:0), (9:1), (7:3), (5:5 ), (3:7), and (1:9). Data analysis was carried out using analysis of variance, followed by Duncan's Multiple Range Test to determine significant differences between treatments. The results showed that the ratio of maltodextrin and gum arabic had a significant effect (P < 0.05) on yield, water content, solubility, total phenols, total flavonoids, antioxidant activity and encapsulation efficiency.The treatment (1:9) produced encapsulated robusta coffee skin ethanol extract with the best characteristics, namely with the criteria of yield 77.28%, moisture content 5.53%, solubility 93.06%, total phenols 99.16 mg GAE/g, total flavonoids 59.71 mg QE/g, antioxidant activity 81,25%, IC50 value 15.84 ppm, encapsulation efficiency 71,22%, and irregular particle shape, smoother and slightly hollow. Keywords: Coffee skin, encapsulation, gum Arabic, maltodextrin